2017 AHA Heart Science Forum Innovation Challenge Award 1st Place Winner and the 1st Annual Samsung Digital Health Summit Technology Pitch Contest Award 1st Place Winner - Joseph T Shen; Raffi B Shen (Archives of Clinical Hypertension - Peertechz Publications, 2018)
Multifunction Cardiogram Technology or the MCG was engineered to answer a fundamental question and solve a critical problem. The question was if we could apply the mathematic principals of Lagrangian Mechanics to build an objective machine powered digital diagnostic paradigm to forever change the face of the future of diagnostic medicine, as we know it. The problem we wanted to solve once and for all was the intractable dilemma of poor diagnostic accuracy caused by the deeply fl awed system designs of the conventional imaging and EKG/EEG tools used throughout the industry.Thus, starting from the very fi rst moment, we had to learn from where others failed.During the design phase of the fi rst generation of our technology, our team performed an extensive review of all existing technology that currently works via the processing of ECG signals.